2006
DOI: 10.22358/jafs/66915/2006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of rapeseed expeller cake for broilers: effect of dry extrusion

Abstract: The effect of extrusion, applied in the production of cold-pressed rapeseed cake on its nutritional value for broilers was evaluated. Two experiments were performed on 55 female broiler chickens, kept individually and allocated to 2 groups of 14 birds (growth trial) or to 3 groups of 9 chickens (digestibility trial). Rapeseed cakes pressed once (RC) or extruded and pressed again (RCE) were mixed in a 6:4 proportion with a basal diet and used in a balance trial with 3-week-old chickens. Furthermore, they were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…The chemical composition of the rapeseed expeller cake being studied (Table 1) was similar to the composition of other RCs obtained using the same technique and previously reported by Schöne et al (1997Schöne et al ( , 2002 and Smulikowska et al (2006). The mean laying rate, across all dietary treatments, and the entire experimental period (between 28-53 wks of hen age) was 94.6%; egg weight, 59.6 g; daily egg production, 56.4 g/hen; daily feed consumption, 116 g/hen and feed conversion per 1 g of eggs, 2.06 g ( Table 3).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The chemical composition of the rapeseed expeller cake being studied (Table 1) was similar to the composition of other RCs obtained using the same technique and previously reported by Schöne et al (1997Schöne et al ( , 2002 and Smulikowska et al (2006). The mean laying rate, across all dietary treatments, and the entire experimental period (between 28-53 wks of hen age) was 94.6%; egg weight, 59.6 g; daily egg production, 56.4 g/hen; daily feed consumption, 116 g/hen and feed conversion per 1 g of eggs, 2.06 g ( Table 3).…”
Section: Resultssupporting
confidence: 82%
“…In diets with 0, 4, 6 and 8% RC, N balances and metabolizability of energy behaved similarly (p > 0.05). For comparison, in an experiment with broiler chickens, Smulikowska et al (2006) found the relative N retention (as % of N intake) to be 44.7%, and content of AME N in gross energy of rapeseed cake to be 55.1% (Smulikowska et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feed consumption: Amount of feed consumption on turkeys in starter, finisher periods (Table 5) and the whole period in experimental groups with different levels of the extruded full-fat soybean (EFFSB) were decrease than control group but this difference was insignificant (p>0.05). The findings of the present study are in conformity with the findings of the previous research works (Marsman et al, 1997;Nalle et al, 2011) but at the same time they were not in conformity with the findings of the researchers who witnessed increased intake of EFFSB (Smulikowska et al, 2006). This might be due to an underestimation of the energy content of the beans used and was probably due to the fact that the energy value available to the bird as a result of rolling and extrusion, coupled with pelleting of the diets, was underestimated.…”
Section: Resultssupporting
confidence: 67%
“…Rapeseed cake was pressed on a screw press expeller, extruded and pressed again. The chemical composition of the rapeseed cake was described previously (Smulikowska et al., 2006a). The cake contained 21 μmol alkenyl glucosinolates per g (25 μmol/g fat‐free DM).…”
Section: Methodsmentioning
confidence: 99%